2007
DOI: 10.1176/ps.2007.58.1.121
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Assertive Community Treatment and Intensive Case Management for Patients in Rural Areas

Abstract: The evidence suggests that intensive case management programs are effective only in community settings where there is an ample supply of treatment and support services. To build the evidence base for the effectiveness of these models, much more attention needs to be focused on evaluating the current wave of assertive community treatment and intensive case management dissemination in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The results of this study are consistent with previous studies suggesting that ICM can be highly effective when delivered to members with serious and persistent mental illness at high risk of hospitalization (Cook et al, 2008;Meyer & Morrissey, 2007;Rosen et al, 2008). Cost-effective ICM services should routinely be provided to adults with chronic psychiatric conditions and a history of repeated hospitalizations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this study are consistent with previous studies suggesting that ICM can be highly effective when delivered to members with serious and persistent mental illness at high risk of hospitalization (Cook et al, 2008;Meyer & Morrissey, 2007;Rosen et al, 2008). Cost-effective ICM services should routinely be provided to adults with chronic psychiatric conditions and a history of repeated hospitalizations.…”
Section: Discussionsupporting
confidence: 89%
“…Burns and colleagues (2007) cite the failure to control for previous hospital utilization as the main reason for the inconsistency, as ICM appears most effective at reducing hospitalized days among patients with a history of repeated hospitalizations or known to be at high risk of hospitalization (Burns et al, 2000;Mueser, Bond, Drake, & Resnick, 1998;Prince, 2006;Rosen, Bond, & Teesson, 2008;Tyrer, 2000a). ICM is more effective in settings with an ample supply of treatment and support services such as managed care environments (Meyer & Morrissey, 2007). Other possible reasons for the lack of outcome consistency include varying health care contexts, with ICM more effective in countries without global health care coverage (Burns et al, 2007;Burns, Fioritti, Holloway, Malm, & Rossler, 2001).…”
mentioning
confidence: 99%
“…Another Dutch study found a (negative) relationship between level of ACT model fidelity, especially team structure, and some items of the HoNOS and the number of homeless days (Van Vugt et al 2011). Implementation of fully fledged ACT is especially difficult in rural areas because of the low population density, the lack of adequate services for patients and the lack of personnel (Meyer and Morrissey 2007). This was one of the reasons for the development in the Netherlands of the FLEXIBLE ACT model (Van Veldhuizen 2007; Van Veldhuizen et al 2008; Van Veldhuizen and Bähler 2013).…”
Section: Introduction: Act and Flexible Actmentioning
confidence: 99%
“…The issues faced in Ontario, such as drift in target population, inadequate funding levels, workforce shortages in rural areas, and lack of ongoing system-wide monitoring, are consistent with those of other jurisdictions. 18,38 We would argue that it is necessary to attend to issues of leadership, funding, standards, oversight capacity, implementation support, and ongoing feedback on practice regardless of the system in which ACT teams are situated.…”
Section: Implications For Behavioral Healthmentioning
confidence: 99%